H-Point Standard Addition Method for Simultaneous Determination of Eosin and Erytrosine. Issue 4 (2011) - Kaur, Amandeep; Gupta, Usha
Abstract : A new, simple, sensitive and selective H -point standard addition method (HPSAM) has been developed for resolving binary mixture of food colorants eosin and erythrosine, which show overlapped spectra. The method is based on the complexation of food dyes eosin and erythrosine with Fe(III) complexing reagent at pH 5.5 and solubilizing complexes in triton x-100 micellar media. Absorbances at the two pairs of wavelengths, 540 and 550 nm (when eosin acts as analyte) or 518 and 542 nm (when erythrosine act as analyte) were monitored. This method has satisfactorily been applied for the determination of eosin and erythrosine dyes in synthetic mixtures and commercial products.